Al-Qur'an Learning Strategy Through the Wafa Method in Elementary Schools - M. Asep Fathur Rozi; Arina Nur Laili (Tarbiyah Departement collaboration with AMCA, 2020)
Al-Qur'an learning strategies are steps that are arranged in a planned and systematic manner using certain techniques and methods in the learning process of the Qur'an to achieve the desired goals. One of the Al-Qur'an learning methods is the Wafa method. Wafa is learning Al-Qur'an using the right brain method as a system and method of learning Al-Qur'an which is comprehensive, easy and fun. The focus of this research is the teacher's strategy in learning Al-Qur'an through the Wafa method at SDIT Al-Aqsha Besole Besuki Tulungagung. This type of research used by the author is a type of qualitative research. The data collection by the writer uses interview, documentation and observation methods. As for the analysis, the researcher used a qualitative descriptive analysis technique, namely describing the data that had been obtained so that it was in accordance with what was happening in the field. The results of this study indicate that learning the Koran using the Wafa method uses the TANDUR pattern (Embed, Natural, Name, Demonstrate, Repeat and Celebrate) and the teacher's strategy in learning the Koran is carried out well because it is supported by media, props and books. guide Wafa.